2019
DOI: 10.3892/etm.2019.7414
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between curcumin and all‑trans retinoic acid in the osteogenic differentiation of mouse bone marrow mesenchymal stem cells

Abstract: The use of bone marrow mesenchymal stem cells (BMSCs) has great potential in cell therapy, particularly in the orthopedic field. BMSCs represent a valuable renewable cell source that have been successfully utilized to treat damaged skeletal tissue and bone defects. BMSCs can be induced to differentiate into osteogenic lineages via the addition of inducers to the growth medium. The present study examined the effects of all-trans retinoic acid (ATRA) and curcumin on the osteogenic differentiation of mouse BMSCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 97 publications
2
14
0
Order By: Relevance
“…In this regard, studies on curcumin formulations indicated that it can be used to improve its transdifferentiation. The experimental results showed that curcumin considerably improved hLMP-3 osteogenic function and cell transdifferentiation action through the enrichment of differentiation medium with curcumin [21].…”
Section: The Osteogenic Differentiation Activity Of Curcuminmentioning
confidence: 97%
“…In this regard, studies on curcumin formulations indicated that it can be used to improve its transdifferentiation. The experimental results showed that curcumin considerably improved hLMP-3 osteogenic function and cell transdifferentiation action through the enrichment of differentiation medium with curcumin [21].…”
Section: The Osteogenic Differentiation Activity Of Curcuminmentioning
confidence: 97%
“…Furthermore, curcumin was found to not only increase osteogenic differentiation but also improve its transdifferentiation. The enrichment of differentiation medium (DMEM with 15% FBS) of mouse embryonic fibroblasts with 15 µM curcumin dissolved in DMSO and co-treatment with human LIM mineralization protein 3 (hLMP-3), a positive regulator of bone formation, resulted in improved hLMP-3 osteogenic potency and cell transdifferentiation processes [48]. According to Jain et al, the controlled release of curcumin from polymer scaffolds resulted in the osteogenic differentiation of MC3T3-E1 pre-osteoblasts seeded onto the platform.…”
Section: Curcumin’s Effects On Osteogenic Differentiationmentioning
confidence: 99%
“…In case of osteogenic differentiation, curcumin with varying concentrations up to 20 µM shows an inhibition of osteoclast differentiation in a dose-dependent manner, while the optimal dose for the inhibition of osteoclast differentiation was found to be 10 µM [48,72,73,74]. This optimum curcumin dosage is also reported to up-regulate HO-1 expression, induce ER stress markers, and finally, induce osteoblast differentiation [47,50].…”
Section: Effect Of Curcumin Dose On Mesodermal Differentiation Of mentioning
confidence: 99%
“…[18][19][20] This substance exhibits antimicrobial, antiinflammatory, antioxidant properties, and facilitates the healing of injured bone, periodontium, and liver tissues caused by inflammation and oxidation. [18,21,22] This ingredient modulates inflammatory cytokines such as TNF-α and IL-1 and IL-6 by upregulation of peroxisome proliferator-activated receptor-gamma (PPAR-γ). [3] Moreover, CUR enhances both osteoblastic and anti-osteoclastic activities and improves osteogenic differentiation in mesenchymal stem cells, and induces mineralization.…”
Section: Introductionmentioning
confidence: 99%